Pemanfaatan Video Pendek TikTok untuk Strategi Digital Marketing Showroom Jati Subur Mobil - Wahyu Krisnawan; Muhammad Bhirawa Dwi Atma Citalada (LPPI UMN AL WASHLIYAH, 2025)
The development of digital technology has transformed traditional marketing methods into more dynamic, content-based strategies, particularly through social media platforms like TikTok. This study aims to analyze how short videos on TikTok are utilized as part of the digital marketing strategy by the car showroom Jati Subur Mobil, using the TikTok account @jatisuburmobil. The method used is descriptive analysis. Data were collected from the showroom's TikTok content and documentation of digital promotional activities. The results show that using short videos with engaging visuals, relevant music, and concise information effectively increases user engagement, expands audience reach, and builds brand awareness for Jati Subur Mobil more effectively than traditional promotional media. TikTok also allows the showroom to directly reach younger market segments by following weekly or monthly trending topics. This study concludes that TikTok is not only an entertainment platform but can also be optimized as a strategic digital marketing tool for local automotive businesses.